Chapter 20 Children as Citizens of a Global Society Learning Together in Culturally and Linguistically Diverse Classrooms - Theobald, Maryanne (Taylor & Francis, 2023)
As members of a global society, many young children's experience in early childhood classrooms have yet to fully realize the richness of their increasingly culturally and linguistically diverse settings. Drawing on data from a participatory action research project, this study explored how such settings might produce global citizens who enact the social responsibilities of respect, empathy, and acceptance. Video-recordings of children aged five to six years in four urban preschool classrooms across Southeast Queensland, Australia, were collected. The teachers showed the children involved selected excerpts to illicit video-stimulated accounts. Excerpts were transcribed using conversation analytic methods, documenting turn taking, and verbal and non-verbal responses. Explicating teacher and young children's classroom interactions and accounts identified the classroom practices of teachers and children to encourage global citizens who promote respect, empathy, and acceptance. This chapter presents the co-designed Empowering Global Learner framework of participation, communication, and sense of belonging to illustrate the classroom practices used for effective global citizens.